Kelayakan LKPD Berbasis Inkuiri Terbimbing untuk Melatihkan Keterampilan Proses Sains pada Materi Sistem Organisasi Kehidupan - Dwi Nilam Sari; Kurnia Ningsih; Eko Sri Wahyuni (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research aims to determine the feasibility of guided inquiry-based LKPD for practicing science process skills in class VII life organization system material at SMP Negeri 4 Sungai Raya. The method used in this research is research and development (R&D) with the Borg & Gall development model which is carried out through six stages, namely potential and problems, data collection, product design, design validation, design revision, and product testing. The research subjects were 10 class VII students at SMP Negeri 4 Sungai Raya with 3 high ability students, 4 medium ability students and 3 low ability students. The instruments used were validation sheets and science process skills assessment sheets which were validated by 5 validators. The results of the validation analysis from the aspects of appropriateness of content, language, presentation and graphics using Aiken's V obtained an average value of 0.91 which was declared valid, and an ICC reliability value of 0.82 was obtained in the good category. The results of the analysis of students' science process skills from the aspects of observing, asking, hypothesizing, grouping, applying concepts, and concluding obtained an average score of 88.33% in the very good category. This can be concluded that the LKPD is suitable for use as teaching material.